Pantoprazole pour les patients des soins intensifs exposés à un risque élevé de saignements gastro-intestinaux - Tran, Van Anh Sylvie; Hoffman, Lindsay; Zhang, Yu Shan; Tremblay, Lydjie (Pharmactuel, 2020)
-